Experimental determination of limiting range of vision for underwater laser system - A. S. Golosnoy (Омский научный вестник)
Modern tasks of improving the quality of underwater research results require the use of innovative solutions. One of the modern directions is the development of informative channels based on laser systems for underwater vision. The objectives of the study, in the presented work, are: substantiation of the use of a laser informative channel for mapping the bottom surface; evidence of the calculation of the limiting range of visibility of the laser system through the transfer functions characterizing the contribution of each of the components of the multi-link system to the formation of the final image. The proposed laser systems can find practical application in the fields of oceanographic scientific research, underwater search, and in the equipment of deep-sea vehicles. The calculations and field tests carried out on the basis of the developed mathematical model in real conditions showed the correspondence of theoretical and experimental results.